Bioactivity of Calanus finmarchicus as a sidestream of the pelagic fish industry - Unnur Elísabet Stefánsdóttir 1988- (2020)
The Northeast Atlantic Mackerel (Scomber scombrus) and the Atlantic herring (Clupea harengus) are among the pelagic fish species around Iceland. The mackerel has in recent years migrated into Icelandic fishing zones where it is increasingly caught in late summer in a well-fed state. The copepod Calanus finmarchicus is a principal part of both the mackerel’s and herring’s feed and contains various valuable components such as lipids, carotenoids, chitin and enzymes that could be used in the production of fish feed, food supplements and biomaterials. In this study, the bioactivity of various Calanus finmarchicus rich oils and aqueous samples obtained from a zooplankton-rich side-stream from pelagic fish processing was evaluated. An in vitro model was set up using Caco-2 cells and their proliferation and morphology analyzed. The results indicated that the oils were considerably toxic to the cells even when treated with low concentrations for short periods of time. The cells were able to grow in the aqueous samples but did however show signs of stress and decreased proliferation in many of the treatments tested. Heat treatment during processing could influence the bioactivity of the side-stream as the growth curve of cells treated with the most heated samples differed from others in the way that the cells were more active at the end of the culturing period. Overall, the tested samples did not have positive effects on the cells while a handful of samples did not show adverse effects and should be studied further. It should be noted that these were crude samples and that might explain the stress reaction of the cells in the model. It is thus necessary to further investigate the bioactivity of side-stream samples with the use of additional methods when the samples have been purified and active ingredients isolated.